2012
DOI: 10.4103/0189-6725.99392
|View full text |Cite
|
Sign up to set email alerts
|

Dismembered pyeloplasty for ureteropelvic junction syndrome treatment in children

Abstract: Open dismembered pyeloplasty is a safe and effective treatment in paediatric UPJS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This represents the ability of the kidney to increase the glomerular filtration rate (GFR) [2]. In the present study, preoperative mean of split glomerular filtration rate (GFR) increased from 25. reported that improved renal function in 89%, stable in 7%, and deterioration in 4% of patients which was comparable to this study [12].…”
Section: Discussionsupporting
confidence: 90%
“…This represents the ability of the kidney to increase the glomerular filtration rate (GFR) [2]. In the present study, preoperative mean of split glomerular filtration rate (GFR) increased from 25. reported that improved renal function in 89%, stable in 7%, and deterioration in 4% of patients which was comparable to this study [12].…”
Section: Discussionsupporting
confidence: 90%
“…In developed countries, almost all abnormalities of the PUJ are detected and treated early in life due to the widespread use of prenatal ultrasound and the advent of modern imaging techniques. [17][18][19] None of the patients in our study were diagnosed prenatally even though ultrasound is readily available and the cost of prenatal ultrasound screening is relatively low. It is, therefore, not surprising that 31% of the patients in our study presented during childhood, even though this age of presentation is late compared to what is seen in developed countries.…”
Section: Discussionmentioning
confidence: 97%
“…It is, therefore, not surprising that 31% of the patients in our study presented during childhood, even though this age of presentation is late compared to what is seen in developed countries. 18,19 It appears that prenatal diagnosis will continue to elude most patients in developing countries until prenatal screening is incorporated into national healthcare policies.…”
Section: Discussionmentioning
confidence: 99%